2016
DOI: 10.1088/0022-3727/49/50/505601
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study of lithium diffusion at the interface between olivine-type LiFePO4and LiMnPO4

Abstract: Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or medium for personal research or study, educational, or not-for-profit purposes without prior permission or charge, provided the authors, title and full b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
5
9
0
Order By: Relevance
“…As shown, the energy barriers between three minimum sites are 0.42 and 0.41 eV, respectively. The low-energy barrier of Li + diffusion from DFT is comparable to the reported values for LiMnPO 4 (0.60 eV), 49 Bi 2 M o O 6 (0.40 eV), 50 Bi 2 S 3 (0.57 eV), 51 and LiFe-PO 4 , 49 and it indicates a fast rate of Li + diffusion. To confirm the coupling between P doped CN and FeP, we calculate the charge difference of FeP on P doped CN, it is found that the coupling is very localized to the interface.…”
Section: Resultssupporting
confidence: 83%
“…As shown, the energy barriers between three minimum sites are 0.42 and 0.41 eV, respectively. The low-energy barrier of Li + diffusion from DFT is comparable to the reported values for LiMnPO 4 (0.60 eV), 49 Bi 2 M o O 6 (0.40 eV), 50 Bi 2 S 3 (0.57 eV), 51 and LiFe-PO 4 , 49 and it indicates a fast rate of Li + diffusion. To confirm the coupling between P doped CN and FeP, we calculate the charge difference of FeP on P doped CN, it is found that the coupling is very localized to the interface.…”
Section: Resultssupporting
confidence: 83%
“…From DFT calculations, the lowest energy barrier from the initial to the final state is 0.57 eV, whereas the energy barriers for the other two paths are 1.22 eV (Supplementary Figure S17), indicating that Li mainly diffuses through the channels along the b-axis or the (Bi 4 S 6 ) n moiety direction of the Bi 2 S 3 crystal. The low-energy barrier of Li diffusion from DFT is comparable to the reported values for LiMnPO 4 (0.60 eV), 42 bulk Bi 2 MoO 6 (∼0.40 eV), 43 and LiFePO 4 (0.48 eV), 42 and it is also consistent with the fast rate of initial Li intercalation. The high diffusivity can be related to the weak van der Waals (vdW) interactions between (Bi 4 S 6 ) n moieties in the Bi 2 S 3 crystal.…”
Section: T H I S C O N T E N T Isupporting
confidence: 86%
“…For Olivine LiFePO 4 , the Li + diffusion channel along the (010) direction is the most favorable. 92 From nudged elastic band (NEB) calculations, E diff is predicted to be 0.55 eV along the 010 direction, in good agreement with the previous reports of 0.6 eV using MD with GGA function 93 and 0.45 eV using DFT with LDA. The D Li also can be estimated by eq 3.…”
supporting
confidence: 85%